Imbalance of von Willebrand factor and its cleaving protease ADAMTS13 during systemic inflammation superimposed on advanced cirrhosis. (3rd September 2014) - Reuken, Philipp A.; Kussmann, Anna; Kiehntopf, Michael; Budde, Ulrich; Stallmach, Andreas; Claus, Ralf A.; Bruns, Tony
Abstract Background & Aims Systemic inflammation in advanced cirrhosis represents a spectrum ranging from subclinical pathological bacterial translocation and immune activation to overt bacterial infection and sepsis. We hypothesized that systemic inflammation in cirrhosis is accompanied by a failure of ADAMTS13 to control the prothrombotic function of von Willebrand factor (VWF), which is increased in portal hypertension and hepatic fibrosis. Methods Patients with Child A cirrhosis (n = 25), Child B/C cirrhosis without clinical features of systemic inflammation (n = 31), and Child B/C cirrhosis with overt bacterial infections or systemic inflammatory response syndrome (n = 24) were analysed for ADAMTS13 and associated parameters and were followed to determine transplant‐free survival. Results Plasma concentration and activity of ADAMTS13 were decreased in patients with systemic inflammation. Furthermore, ADAMTS13 inversely correlated with the extent of bacterial translocation and the severity of acute‐phase reaction. As a function of reduced ADAMTS13 activity and increased VWF antigen, plasma from patients with superimposed inflammation strongly aggregated the platelet receptor glycoprotein Ib in presence of ristocetin. VWF:RCo correlated with higher concentrations of leucocytes and lipopolysaccharide‐binding protein, organ dysfunction, augmented turnover of cross‐linked intravascular fibrin, and the occurrence of acute kidney injury during follow‐up. VWF:RCo of 390% or more predicted transplant‐free survival in univariate analysis [HR = 8.24 (3.30–20.54)] and after adjustment for MELD [HR = 3.58 (1.30–9.88)]. However, adverse outcome was not associated with the accumulation of high‐molecular weight VWF multimers. Conclusions Systemic inflammation complicating advanced cirrhosis is accompanied by reduced activity of ADAMTS13 promoting a prothrombotic function of VWF, which can be employed to predict clinical outcome.